The role of social media in shaping airline’s image - Elemonie, Anastasia (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2020)
Social media is important nowadays. With the development of technology today, most people want their needs to be fulfilled in an instant. Speed is the key in most cases. In this era all media gets digitized, the Internet also becomes the mode of carriage for all other media, meaning a lot of information is available on the internet. In today’s competitive business environment, under pressure from the digital revolution, the corporate brand with its identity, image, and reputation becomes the center of gravity for valuable and durable relationships between the firm and all interested parties. The researcher has chosen qualitative data for designing this research. Focus of this research it is aimed to understand the social media that has been used by Cathay Pacific Airways to shape its corporate image in the eyes of public. The analysis shows that the active promotion activities through social media has a big influence in the formation of the expected company image. The use of social media as one of the strategies that Cathay Pacific uses as a means of communication can increase customer engagement. Keywords: Corporate Communication; Corporate Image; Social Media; Perception; Airlines.